Benefits of XPS nanocharacterization for process development and industrial control of thin SiGe channel layers in advanced CMOS technologies. (1st November 2017) - Fauquier, L.; Pelissier, B.; Jalabert, D.; Pierre, F.; Hartmann, J.M.; Rozé, F.; Doloy, D.; Le Cunff, D.; Beitia, C.; Baron, T.
Abstract: The Si channel of advanced p-type transistors has been replaced by a compressively strained Silicon-Germanium channel (SiGe) in order to improve the device performances. The SiGe thickness and composition must be precisely controlled to reproducibly obtain the same characteristics. In this study, the benefits of X-ray Photoelectron Spectroscopy (XPS) for the process development and the industrial control of thin SiGe channel layers are shown. The use of a parallel Angle Resolved XPS (pARXPS) allowed us to obtain the germanium distribution in very thin SiGe channels, a useful information to better understand the impact of various process steps on the germanium distribution. The hybridization of in-line XPS and X-Ray Reflectivity (XRR) has been used as an industrial process control characterization method to jointly determine the SiGe channel's thickness and germanium composition. This hybrid industrial metrology technique has shown promising results.